Types of Grammatical Elements in Indonesian ELT Textbook: SFL Perspective - Hermawati, Siti Puput; Santiana, Santiana; Silvani, Dea (Siliwangi University, 2023)
Transitivity analysis is used to study news, reading, speeches, and other discourses. However, recent textbooks on grammatical element participants and processes have little transitivity analysis research. Teachers who understand transitivity analysis can help students understand grammar and improve their oral and written communication skills by developing grammar and using proper teaching methods to teach about sentence subjects and predicates. This study seeks to identify the transitivity participants and processes that define grammatical elements in English for Nusantara for Grade 7. This study employed a textbook for qualitative content analysis. Subsequently, Halliday and Matthiessen's (2014) transitivity analysis is applied to the data. The types of participants found in this study were carrier (93 words), actor (79 words), senser (29 words), token (18 words), sayer (17 words), and behaver (8 words). Additionally, the relational processes (112 words) include attributing (94 words) and identifying (18 words), material processes (111 words), mental processes (32 words), verbal processes (18 words), existential processes (8 words), and behavioral processes (7 words). This study suggests that teachers employ transitivity to create activities and strategies to help students learn English grammar. It should assist students meet Merdeka Belajar curriculum goals, including speaking and writing English well. Keywords: Grammatical Elements, English Textbook, Systemic Functional Linguistics, Transitivity